United States – Kenyan Asymmetry in Counterterrorism Cooperation: An Assessment of the Efforts of the United States and Kenya in East Africa - Mkuti, Sky; Van Wyk, Jo-Ansie; Tella, Oluwaseun (Scientia Militaria - South African Journal of Military Studies, 2024)
On 11 September 2001, the world witnessed a drastic change in the global security landscape that influenced the dynamics of United States counterterrorism. The United States expanded its global alliances, including its financial assistance and cooperation scope, in East Africa as well. A fundamental transformation in the United States Defence Foreign Policy towards Africa was marked by a growing reliance by the United States on African partners, such as Kenya. Despite visible power disparities between the United States and Kenyan asymmetric relations, the two states set an unmatched counterterrorism partnership in East Africa – even with the growing criticism of the United States militarisation in some parts of Africa, such as in the Sahel region, which remains prone to coups despite enduring counterterrorism interventions by the United States. What is particularly interesting is how the asymmetric relations between the United States and Kenya enhanced a stable and multidimensional implementation of counterterrorism in East Africa. The dynamics of these asymmetric relations on counterterrorism demystify the perception that asymmetric relations between powerful and weak states are inherently unstable. Employing secondary data, the study on which this article reports, sought to deconstruct such rhetoric by conceptualising asymmetry whilst identifying five main conceptualisations of asymmetry theory that characterises the asymmetric relations between the United States and Kenya. Thereafter, by taking stock of the multidimensional efforts by the United States and Kenya, it is argued that triangular asymmetries are the significant force multipliers of stability and normalcy in asymmetric relations.